The Role of Internet of Things in the Healthcare Industry - Umashankar, M (International Journal of Computer Sciences and Engineering, 2019)
Internet of Things is an innovative computerized system which is used for several applications across industries through their flexibility and capabilities. Independently living old age population is increasing now a days. They are requiring medical assistance in time, really it is a big issue. Continuous monitoring is an essential process to solve this issue. Medical devices have been enriched by incorporating cyber and physical capabilities to provide better health care services. With the help of wireless communication protocols, the IoT provide the interconnection facilities between the medical devices and other monitoring hardware. Supporting with the technology and smart devices, the IoT applications perform data collection, automation, and operations. IoT play a vital role in improving the health, safety and care of patients through healthcare monitoring system. Through the healthcare monitoring system the patient getting immediate help from the medical persons. In addition they may get medical assistance and recommendations also. This paper presents the strengths, weaknesses, challenges and overall suitability for a wearable IoT health care system.